FRI0283 Dynamic contrast enhanced mri (DCE-MRI) demonstrates hippocampus permeability in sle. (12th June 2018) - Mackay, M.; Diamond, B.; Eidelberg, D.; Hoang, A.; Sanelli, P.C.
Abstract : Background: Cross-reactive, anti-dsDNA/N-methyl d-aspartate receptor antibodies (DNRAb) have been implicated in the pathogenesis of cognitive impairment in SLE. The mouse model demonstrates selective effects of DNRAb on hippocampal neurons following blood brain barrier (BBB) breach. 1 We previously identified abnormal hippocampal glucose hypermetabolism in SLE patients that correlated with serum DNRAb titers and poor performance on neuropsychological (NP) testing. 2 However, little is known about how antibodies access brain in humans. Objectives: BBB permeability (BBBP) in SLE and healthy control (HC) subjects was evaluated with DCE-MRI. We hypothesised that brain areas with abnormal hypermetabolism 2 in SLE subjects would also demonstrate altered BBBP. Methods: 6 SLE subjects with no history of NP symptoms and 6 HCs were recruited (all female). All subjects underwent NP testing and DCE-MRI on a 3.0 tesla magnet (Siemens Healthineers, GERMANY). MRI sequences were acquired according to standard protocols; permeability imaging used DCE technique with axial 3D-SPGR T1-WI sequences and 80 cine phases using TR=25 ms, TE=3.8 ms, FOV=24 mm, and matrix size of 128×256. Magnevist Gadolinium contrast (Bayer Healthcare, GERMANY) was dosed IV at 0.1 mmol/kg, at 5cc/sec following a 5 s delay. Post-processing of images into BBBP parameters of K-trans (mL/100 gm/min) and VE (mL/100 gm) was performed using Olea Sphere 2.2, 2.3 (Olea Medical, France) with the Tofts extended permeability model. This technique was standardised with the arterial input function centred in the cavernous ICA segment for all subjects. Analyses: Regions-of-interest (ROI) from previously identified hypermetabolic regions (hippocampus, orbitofrontal cortex, posterior putamen/globus pallidus/thalamus) were selected. Mirror ROIs were placed in bilateral MRI cerebral hemispheres for sampling at same brain levels. Regional DCE curves were generated to compare permeability phases. T-tests were used to evaluate demographic and NP testing differences. Results: SLE subjects performed significantly worse than HCs on cognitive testing (table 1). Mean DCE curves (figure 1) show perfusion (initial spike) and permeability phases of contrast in the sampled tissues. Compared to HCs, SLE subjects demonstrate significantly increased signal in the permeability phase in the hippocampus, indicating leakage of contrast into the extravascular space. Conclusions: This is the first report of increased BBBP in SLE subjects that is specific to the hippocampus; a region that we have previously reported to have abnormal resting metabolism in SLE subjects. These data, including the abnormal NP testing, support the murine model of autoantibody-mediated cognitive impairment following disruption of the BBB. The results also suggest that DCE-MRI may be an effective, non-invasive tool to measure BBBP and its role in neuropsychiatric SLE pending confirmatory studies with increased sample size. References: [1] Kowal C, et al. Immunity2004;21:179–88. [2] Mackay M, et al. Lupus Sci Med2015;2:e000074. Disclosure of Interest: None declared